Left Ventricular Assist Devices – Past, Present, and Future: A Narrative Review - Devesh Kumar; Sandeep Seth; Rajiv Narang (Journal of the Practice of Cardiovascular Sciences)
Advanced heart failure (AHF) is a major problem with an aging population and profound unmet needs. While heart transplant offers the most definitive solution, it is largely unavailable for most and mandates a long waiting period. Left ventricular assist devices (LVADs) help in expanding the treatment armamentarium to those for whom transplant is either a contraindication or unavailable (destination therapy) and those who need stabilization before transplant (bridge to transplant). LVADs are truly a renaissance in the management of AHF as they make treatment available to a much larger population and improve not only symptoms and quality of life but also survival as compared to patients on medical therapy only. Consequently, they have now been adopted in many European centres as destination therapy with a median survival of 7 years in patients with a LVAD implantation. LVADS are plagued with multiple complications, and while they do offer an opportunity of improved survival, the patients often are plagued with morbid complications. Newer advances in technology have paved the way for smaller and better engineered devices with lesser complications like bleeding and pump thrombosis. We review briefly the burden of advanced Heart Failure, evolution of LVADs, current status and the future of these devices.